A Framework to Prioritize the Public Expectations from Water Treatment Plants based on Trapezoidal Type-2 Fuzzy Ahp Method - Yildiz, Aslihan; Ayyildiz, Ertugrul; Taskin Gumus, Alev; Ozkan, Coskun (SPRINGER, 2021)
Water treatment plants play a major role in the cycle of water recovery and reuse. Besides the benefits of water treatment plants, they have a great impact on the environment, social life, economy, and natural habitats. In this sense, decision-makers should effectively plan the construction and operational activities of plants, taking into account the expectations of users. Growing public expectations about water treatment plants increase the pressures on investors and government managers. In this study, we focus on defining and determining the weights of public expectations from water treatment plants and handle as a multi-criteria decision-making problem. A two-level hierarchical model is structured to evaluate public expectations from water treatment plants as model criteria. For the problem, a literature review is performed to search the main criteria. The most suitable criteria for the problem are determined using experts' opinions. Then, the sub-criteria are determined. Experts' evaluations are collected by face to face interviews. These evaluations are consolidated and finalized via the modified Delphi method. Trapezoidal Type-2 Fuzzy Analytic Hierarchy Process (T2F-AHP) is employed to determine criteria weights using results obtained by the modified Delphi method. A sensitivity analysis is performed to show the reliability of the proposed methodology. A comparison is also performed between the Analytic Hierarchy Process (AHP) and the proposed methodology. The results of this study can be used as a guide to develop public strategies about water treatment plants. Finally, conclusions and future directions of this work are given.
Keywords: Water treatment plant; AHP; Modified Delphi; Trapezoidal type-2 fuzzy sets; ANALYTIC HIERARCHY PROCESS; NETWORK PROCESS; MANAGEMENT; SELECTION; QUALITY; DELPHI; ALTERNATIVES; INVESTMENT; SITES; MODEL; Environmental Sciences & Ecology